Gonialaenini, a new tribe of Lagriinae (Coleoptera: Tenebrionidae) from Eocene Baltic Amber - Nabozhenko, Maxim V.; Bukejs, Andris; Telnov, Dmitry (Zootaxa, 2019)
Based on well preserved specimen, Gonialaena groehni gen. et sp. nov. (Coleoptera: Tenebrionidae) is described from Eocene Baltic amber and assigned to Gonialaenini trib. nov. within the subfamily Lagriinae due to the combination of the following characters: labrum elongate; antennal sensilla simple; procoxal cavities closed at least externally; narrow membranes present between abdominal ventrites 3–5; mesocoxal cavities partly closed by mesepimeron, trochantine present; ovipositor of primitive lagrioid type—digitate fourth coxite lobe with gonostyles apically. Gonialaena gen. nov. combines characters of various Lagriinae tribes: humeral angles rounded, formed by basally widened epipleura as in Goniaderini, Pycnocerini and Lupropini; narrow acute intercoxal process of abdominal ventrite 1 as in Belopini, Cossyphini and Lagriini; absence (or strong reduction) of metathoracic wings as in most Adeliini and some Lupropini; large, reniform eyes as in Goniaderini, Pycnocerini, Lagriini and many Adeliini; present intersegmental membranes between abdominal ventrites 3–5 as in all lagriine tribes except for Belopini and Cossyphini; subcylindrical terminal maxillary palpomere as in Belopini and Cossyphini. Thus, the position of Gonialaenini trib. nov. within Lagriinae is not fully understood, but combination of certain features (humeral angles rounded but distinct and vertical border present at elytral base, inconspicuous elytral striae, large reniform eyes, narrow intersegmental membranes) points on morphological similarity with Goniaderini, especially some Anaedus Blanchard, 1845 with indistinct elytral striae and related genera.